REDUPLIKASI VERBA BAHASA MELAYU JAMBI DI DESA NIASO KECAMATAN MARO SEBO KABUPATEN MUARO JAMBI (KAJIAN MORFOSINTAKSIS) - Firman Tara; Desi Ratna Sari (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2019)
This research is aimed at describing the use of repetition words from the aspect of form, process, and meaning. This research is qualitative descriptive. The data is taken from the quotation of words which are required from data source. The data source is the native speaker of Jambi Malay who live in Niaso village Kecamatan Maro Sebo Kabupaten Muaro Jambi. The data is collected by using observation,  listening, speaking, and writing. The data is analyzed by using direct technique. The result of this research shows that there are 4 reduplications, namely (1) whole reduplication, (2) half reduplication, (3) affixes reduplication, (4) change of phoneme reduplication. There is also one meaning in this reduplication which is stating a work.  Keywords : Analysis, Verb Reduplication, Jambi Malay Language